2022
DOI: 10.3389/fpsyg.2021.800657
|View full text |Cite
|
Sign up to set email alerts
|

An Android for Emotional Interaction: Spatiotemporal Validation of Its Facial Expressions

Abstract: Android robots capable of emotional interactions with humans have considerable potential for application to research. While several studies developed androids that can exhibit human-like emotional facial expressions, few have empirically validated androids’ facial expressions. To investigate this issue, we developed an android head called Nikola based on human psychology and conducted three studies to test the validity of its facial expressions. In Study 1, Nikola produced single facial actions, which were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…3) BORFEO can generate RFEs that receive higher human ratings for most basic emotions compared with previous work involving the same robot [7]; this finding indicates that BORFEO is a high-performance method. The remainder of this paper is structured as follows.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…3) BORFEO can generate RFEs that receive higher human ratings for most basic emotions compared with previous work involving the same robot [7]; this finding indicates that BORFEO is a high-performance method. The remainder of this paper is structured as follows.…”
Section: Introductionmentioning
confidence: 72%
“…1), we have developed, is one of the world's leading androids in this respect. Through a series of human experiments, Sato et al [7] verified that Nikola can produce several basic human-like RFEs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Fig 5 shows, with regard to anger, there were more rapid and intense onsets in Components 1 and 2 relative to the perceived-as-genuine expressions. The greater the speed the greater the perceived intensity of anger expressions [17], but rapid speeds are not always understood to be natural as found in recent android research [62]. In line with the accumulated evidence, many scholars have already reported that the temporal aspects of facial expressions are important [63][64][65][66].…”
Section: Plos Onementioning
confidence: 91%